Annual abstract of statistics 1986 - Federal Office of Statistics (Lagos : Federal Office of Statistics, 1986)
As part of the effort of the federal office of statistics to furnish the public with available information about the economy of Nigeria the 1986 edition of the annual abstract of statistics was prepared by the Federal Office of Statistics, Lagos containing all necessary data up to the year 1985.
nmn, 15/04/19
Ref
Keywords: Statistics; Annual report